Pelaksanaan Program Upaya Khusus (UPSUS) Swasembada Pangan di Kabupaten Wonosobo Provinsi Jawa Tengah - Agus Dwi Nugroho; Sri Nuryani Hidayah Utami; Yunri Yuslianti; Laeli Nurrokhmah; Muhammad Agung Al Huda; Lilis Suryani; Ircham Riyadi; Ulfaizah Ulfaizah; Tri Septijono; Hanifah Albana Nur Adhini (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2017)
The purposes of this activity are 1) the diffusion and testing of cultivation agricultural technology to farmers and 2) to know the problems of UPSUS activities and gives solution to solve it. The activities held on April to July 2017 in Wonosobo Regency and the areas which selected are the Wonosobo, Kalikajar and Sapuran District. Methods for this activity are training and assistance of farmer groups, supervision of agricultural machinery and subsidized seeds aid, provision of balanced fertilizers application, arrange of planting season, rehabilitation of tertiary irrigation, supervision of planting realization; land optimization, and demonstration plots. The results of this activity are providing knowledge for farmers about Salibu and organic rice cultivation, balanced fertilizer, planting according to the planting calendar and providing farmer group’s data that will obtain farmer card; providing information to the Department of Agriculture and Food Crop Wonosobo Regency about the agricultural machinery equipment assistance is still not maximized but the activities of providing subsidized seed, balanced fertilizer and rehabilitation tertiary irrigation have been running well. Some problems in the implementation of UPSUS are the time is too short, agricultural machinery equipment aid is not appropriate, the quality of seed aid is not good, the target program of Luas Tambah Tanam is too high and many PPL and farmers do not understand about Salibu. To improve of UPSUS, the government should prioritize the bottom up principle for all kinds of aids or programs; and socialize the new technology system to PPL and farmers.